DELIBERATIVE DEMOCRACY DALAM MUSYAWARAH RENCANA PEMBANGUNAN DESA (Studi Pada Kecamatan Pulau Rimau, Kabupaten Banyuasin, Sumatera Selatan) - Rahmat Rafinzar; Kismartini; Retno Sunu Astuti (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
The purpose of this research is to measure the adjustment of implementation musrenbangdes with the principles of deliberative democracy and to assess the results of implementation of musrenbangdes in Pulau Rimau Subdistrict, Banyuasin Regency, South Sumatra. Descriptive research method with the approach used in this research process. The data analysis technique used by the researcher is Miles and Huberman. The results of this study indicate that the implementation of the principles of deliberative democracy in the musrenbangdes is weak because it has obstacles in reporting and realizing the results of the musrenbang. The community is not comprehensive in the process of implementing the musrenbang too, this interaction is contrary to the principles of deliberative democracy which is optimizing the role of the community in the process.